Keefektifan Pembelajaran Inkuiri dan Problem-Based Learning terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ilmu Pengetahuan Alam - Ika Hartini; Ferawati Ferawati (Jurnal Inovasi Pendidikan Dasar, 2016)
The purpose of this research is to know the effectiveness of inquiry learning and problem-based learning on science achievement of 4th grade student. This research method is quasi-experiment with non-equivalent control. This research sample is 58 students in SDN Cipinang Besar Selatan 19 Pagi who divided into two groups, 31 students are in inquiry learning class and 27 students are in problem-based learning class. Analysis of t-test indicated the difference of students’ achievement between students who in inquiry learning and problem-based learning classes. The average of science achievement in inquiry learning class is higher than problem-based learning class.